Serving the World or Building a Profession: The Confounding Dilemmas of Mid-Twentieth Century Academic Adult Education - Amy D. Rose; Catherine A. Hansman (Adult Education Research Conference, 2019)
This paper discusses the development and growth of an adult education professoriate and especially the growth and expansion of the CPAE in the 1950s and 1960s.
Keywords: history; professors; adult education profession